Characterization of the complete mitochondrial genome sequence of the dog roundworm Toxascaris leonina (Nematoda, Ascarididae) from China. Issue 2 (3rd July 2019) - Xie, Yue; Li, Hongyu; Wang, Chengdong; Li, Yingxin; Liu, Yunjian; Meng, Xiaduo; Wang, Lu; Zhou, Xuan; Zheng, Youle; Zuo, Zhicai; Gu, Xiaobin; Yang, Guangyou
Abstract: Toxascaris leonina (Nematoda, Ascarididae) is a cosmopolitan nematode of canids and felids and poses potential threats to public health due to aberrant larva migrans. Herein, the complete mitochondrial genome sequence of a representative of this nematode from the dog in China was determined using next-generation sequencing technology. The assembled genome was 14, 357 bp in length and encoded 36 genes, including 12 protein-coding genes, 22 transfer RNAs and 2 ribosomal RNAs. The phylogeny revealed that the canid-originated T. leonina were phylogenetic distinctiveness from the felid-originated T. leonina within the genus Toxascaris of Ascarididae, supporting that T. leonina may represent a species complex.